Liver involvement in children with SARS‐COV‐2 infection: Two distinct clinical phenotypes caused by the same virus. (22nd April 2021) - Perez, Adriana; Cantor, Amanda; Rudolph, Bryan; Miller, Jonathan; Kogan‐Liberman, Debora; Gao, Qi; Da Silva, Bernardo; Margolis, Kara G.; Ovchinsky, Nadia; Martinez, Mercedes
Abstract: Background and Aims: Severe Acute Respiratory Syndrome Coronavirus‐2 (SARS‐CoV‐2) associated acute liver injury (ALI) has been linked to poor outcomes in adults. Here we compare characteristics in children with elevated ALT (E‐ALT) in two distinct manifestations of the infection, multisystem inflammatory syndrome‐children (MIS‐C) and coronavirus disease 2019 (COVID‐19). Methods: This is a retrospective study of patients ≤21 years of age with positive for SARS‐CoV‐2 PCR. E‐ALT was defined as alanine aminotransferase (ALT) > 40 U/L. Bivariate analysis and multivariable logistic regression were obtained to describe differences in children with and without E‐ALT in COVID‐19 and MIS‐C. Results: E‐ALT was detected in 36% of the 291 patients; 31% with COVID‐19, and 51% with MIS‐C. E‐ALT in COVID‐19 was associated with obesity ( P < .001), immunocompromised status ( P = .04), and chronic liver disease ( P = .01). In the regression models, E‐ALT in COVID‐19 was associated with higher c‐reactive protein (OR 1.08, P = .01) after adjusting for common independent predictors. Children with E‐ALT and MIS‐C were more often boys ( P = .001), Hispanic ( P = .04), or Black ( P < .001). In MIS‐C, male gender (OR 5.3, P = .02) and Black race (OR 4.4, P = .04) were associated with increased odds of E‐ALT. Children with E‐ALT in both cohorts had significantly higher multiorgan dysfunction, longer hospitalization, and ICU stay. Children with MIS‐C had 2.3‐fold increased risk of E‐ALT compared to COVID‐19. No association was found between E‐ALT and mortality. Conclusion: E‐ALT with SARS‐CoV‐2 presents as elevated transaminases without hepatic synthetic dysfunction. Patients with either manifestation of SARS‐CoV‐2 infection and E‐ALT experienced more severe disease.